1971
DOI: 10.1021/jm00287a022
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor agents. Schiff bases from benzaldehyde nitrogen mustards and 2-phenyl-4-[(3-amino-4-methoxy)phenyl]thiazole

Abstract: We have already reported several Schiff bases from p-aminophenylthiazoles and benzaldehyde nitrogen mustards as possessing good antitumor activity.2•3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1971
1971
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…3 4 , SB 6 and SB 7 respectively. SB 2 and SB 5 showed the prominent mass peaks at m/z 295.3 and 284.3 due to M + +1.…”
Section: Resultsmentioning
confidence: 99%
“…3 4 , SB 6 and SB 7 respectively. SB 2 and SB 5 showed the prominent mass peaks at m/z 295.3 and 284.3 due to M + +1.…”
Section: Resultsmentioning
confidence: 99%
“…With (T/ C) values of 150 or above, the median survival time of the control group is 30 days. [13] The urea containing thiazole and its compound associated with ethyl Thendry ethyl-p-isocyanato-benzoate 5 was added in anhydrous benzene, and the mixture was refluxed for 2 h to get the desired product 6. "A suspension of 6, in aqueous Na 2 CO 3 , and 10 mL of EtOH was stirred overnight to get compound 7 (Scheme 2).…”
Section: The First Decade (1970-1980)mentioning
confidence: 99%
“…In the last few decades, extensive work has been done on synthesis and biological studies of Schiff bases and their metal-based derivatives Schiff base ligands are excellent coordinating molecules and can exhibit variety in the structure of their metal complexes. Literature survey reveals that Schiff bases have assumed importance in various fields such as coordination chemistry [1], analytical chemistry [2] and pigments, dyes [3] and polymer [4,5] industries; in biochemical researches, especially as model compounds of several vitamins and enzymes [6,7] and in agriculture as fungicides, pesticides and bactericides [8,9]. It has been reported that certain Schiff bases exhibit antitubercular activities [10].…”
Section: Introductionmentioning
confidence: 99%